Successful initiatives of women-led fish farming: Towards a resilient & promising livelihood (Odia Language) - Eriksson, Hampus (WorldFish, 2022)
The video documentary is prepared by FARD department in collaboration with the Department of Mission Shakti, Government of Odisha. WorldFish has provided technical support for implementation of the program. The video focused on the role of the government and WorldFish in accelerating the growth of fisheries in Odisha.